1995
DOI: 10.2337/diacare.18.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Lipoprotein(a) as a Risk Factor for Atherosclerotic Cardiovascular Disease in Patients With Diabetes

Abstract: Lp(a) is a significant risk factor for atherosclerotic cardiovascular disease in NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 6 publications
1
41
0
Order By: Relevance
“…An elevated level of serum Lp(a), primarily genetically determined (11), is a significant risk factor for atherothrombogenesis in both diabetic and nondiabetic subjects (12)(13)(14)(15)(16)(17). Renal dysfunction in particular has been associated with elevated Lp(a) levels, which partly explains the increased susceptibility to vascular disease in patients with renal disease, including diabetic nephropathy (18 -24).…”
Section: Diabetes Care 28:1718 -1723 2005mentioning
confidence: 99%
“…An elevated level of serum Lp(a), primarily genetically determined (11), is a significant risk factor for atherothrombogenesis in both diabetic and nondiabetic subjects (12)(13)(14)(15)(16)(17). Renal dysfunction in particular has been associated with elevated Lp(a) levels, which partly explains the increased susceptibility to vascular disease in patients with renal disease, including diabetic nephropathy (18 -24).…”
Section: Diabetes Care 28:1718 -1723 2005mentioning
confidence: 99%
“…Nonetheless, these non-genetic parameters could be subject to therapeutic intervention in attempts to modify Lp(a) concentrations. 9 Suggested mechanisms for the effects of Lp(a) in modulating vascular disease risk include: (1) anti®brinolytic and prothrombotic effects based on the structural similarity between Lp(a) and plasminogen 10,11 and the described in¯uence of Lp(a) in regulating the endothelial cell synthesis of tissue plasminogen activator inhibitor PAI-1; 12 (2) signi®-cant uptake of Lp(a) with low-density lipoprotein (LDL) by the LDL native and scavenger receptorsÐ indeed, both lipoproteins co-determine atherosclerotic disease risk. However, these different mechanisms remain controversial 13 and do not always satisfactorily account for the striking atherogenicity of Lp(a).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations are available in type 2 diabetic patients, including four prospective studies (22)(23)(24)(25). With the exception of one study (24), the other three showed positive associations (22,23,25).…”
Section: Research Design and Methods -mentioning
confidence: 99%